MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI DEBIT AIR MENGGUNAKAN MODEL GROUP INVESTIGATION - Iswahyudi Joko Suprayitno; Solichatun Solichatun (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Learning will be meaningful if the teacher involves students directly in the learning activities. The result of the observation shows that the teacher has notinvolve the students directly so that the learning result is still low. Teachers arestill dominant with the lecture method, the students are less involved in thelearning process and the students have low learning motivation in learningmathematics.The purpose of this research is to improve learning outcomesMathematics of water debit materials using Group Investgation model in grade 6students of SD Muhammadiyah Sukorejo. This study uses a classroom actionresearch design. Based on the preliminary test, this study was designed into 2cycles and each cycle was held 2 times which included planning, action,observation, and reflection activities. Based on the action done through 2 cycles,it can be concluded that the use of Group Investigation model can improve thelearning outcomes of water debit for grade 6 students of SD MuhammadiyahSukorejo. In the initial or pre-cycle condition of 28 new students, the completionof 32% is 9 students complete the KKM, the average score is 64,71, the highestvalue is 93 and the lowest value is 40. From the initial condition after theimprovement of learning in cycle I of 28 students there a significant increase of21 students (75%) of the KKM, an average score of 74.7, the highest score of 95and the lowest score of 45. On the second cycle improvement improvement of 28KKM students increased again to 25 students (89%), 83.57, the highest value is98, the lowest value is 65.Keywords: Learning outcomes, water discharge, and Group Investigation